2016
DOI: 10.1556/1646.8.2016.1.2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Ramadan fasting on sirtuin and visfatin levels

Abstract: Abstract:Objective: Our aim was to determine how Ramadan fasting eff ects serum Human NAD-dependent deacetylase sirtuin 1 (SIRT1/ SIR2L1) and visfatin levels during pregnancy. Materials and methods: Thirty-six patients were included in this case-control study. The patient group consisted of 18 pregnant women who were Ramadan fasting. Another healthy 18 pregnant women with matching pregnancy weeks and ages formed the control group. Blood samples were obtained from the patients for biochemical analyses and serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Five studies explored the association of Ramadan fasting during pregnancy with fasting blood glucose [ 19 , 53 , 54 , 55 , 56 ]. Results of our meta-analysis showed that fasting during Ramadan significantly reduced fasting blood glucose by 2.73 mg/dl (95% CI: −5.23, −0.22) compared with the non-fasting group ( I 2 = 34.44%) ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies explored the association of Ramadan fasting during pregnancy with fasting blood glucose [ 19 , 53 , 54 , 55 , 56 ]. Results of our meta-analysis showed that fasting during Ramadan significantly reduced fasting blood glucose by 2.73 mg/dl (95% CI: −5.23, −0.22) compared with the non-fasting group ( I 2 = 34.44%) ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although calorie restriction (CR) has been proven to extend the lifespan in lower organisms and mammals through its effect on sirtuins, as evidenced by increased SIRT1 expression in the adipose tissue, liver, kidney, and brain tissue of rodents, as well as in PBMC [33,34,35], it has also been found that the plasma SIRT1 concentration falls in pregnant women during Ramadan fasting to a degree that correlates inversely with the number of fasting days [36]. Physical activity has also been documented as a positive regulator of SIRT1 expression in rats and humans [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we examined intracellular SIRT1 level in peripheral blood lymphocytes for ease of access in clinical cases. Though some studies measured the serum SIRT1 concentration to evaluate the SIRT1 expression level [ 10 , 24 , 29 , 32 , 52 ], the significance of the plasma SIRT1 concentration remains to be clarified because SIRT1 localizes mainly in the nucleus or the cytoplasm. SIRT1 in the cellular lysate and in the serum can potentially be measured by enzyme linked immunosorbent assay (ELISA) in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Though its enzymatic activity has been measured to evaluate its potential inhibitors and activators using cultured cells or recombinant SIRT1 [ 14 ] with respect to longevity, it is usually difficult to evaluate its activity in tissue samples obtained from patients. Thus SIRT1 expression was evaluated by measuring mRNA transcription, tissue SIRT1 protein expression or plasma SIRT1 concentration in association with nutritional conditions or diseases [ 10 , 21 , 23 , 24 , 29 , 35 , 36 , 38 , 49 ]. Not only SIRT1 activation but also increasing SIRT1 expression is related to lifespan extension in experimental condition [ 2 ].…”
mentioning
confidence: 99%